2011
DOI: 10.2215/cjn.03850510
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus and Cyclosporine Nephrotoxicity in Native Kidneys of Pancreas Transplant Recipients

Abstract: SummaryBackground and objectives Calcineurin inhibitors, while representing advances for solid organ transplantation, have nephrotoxic potential that reduces their net benefit. Tacrolimus has been considered less nephrotoxic than cyclosporine, but direct quantitative comparisons of the changes in renal structure from baseline to follow-up biopsies have not been done. To avoid the pitfalls of renal allograft studies, including rejection and disease recurrence, we compared the development of calcineurin lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Similar rates of GFR loss after 5 years post-PTA have been recently reported, with no major difference, irrespective of which calcineurin inhibitor was used [17]. Interestingly, in the present study, the loss of renal function after PTA was less significant in patients with lower baseline GFR (< 90 ml/min) than in patients with higher pristine renal function (GFR > 90 ml/min).…”
Section: Discussionsupporting
confidence: 87%
“…Similar rates of GFR loss after 5 years post-PTA have been recently reported, with no major difference, irrespective of which calcineurin inhibitor was used [17]. Interestingly, in the present study, the loss of renal function after PTA was less significant in patients with lower baseline GFR (< 90 ml/min) than in patients with higher pristine renal function (GFR > 90 ml/min).…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies in type 1 diabetes have shown that IAH did not change 5-10 years after pancreas transplantation, although glomerular changes returned to normal or near normal after surgery (24,25). However, Fioretto et al (26) showed that calcineurin inhibitors, which were used in that study, can induce renal arteriolar hyalinosis. Therefore, the potential histological reversibility of arteriolar hyalinosis with normoglycemia remains uncertain (25,26).…”
Section: Discussionmentioning
confidence: 67%
“…For example, tacrolimus is more likely to cause alopecia [16], tremors [17], and new-onset diabetes mellitus [12], whereas cyclosporine is associated with hyperlipidemia [18], hypertrichosis, and gingival hyperplasia [19]. The idea that tacrolimus is less nephrotoxic than cyclosporine remains controversial [20], particularly as most studies of renal injury are based on evaluations in renal transplant patients, making it difficult to discriminate between drug-induced organ damage and other causes of organ dysfunction [21]. A recent study in pancreatic transplant recipients examined baseline kidney biopsies and 5-year post-transplant biopsies, and reported that the chronic nephrotoxic effects of tacrolimus and cyclosporine were similar [20].…”
Section: Introductionmentioning
confidence: 99%